2019
DOI: 10.1111/acel.12999
|View full text |Cite
|
Sign up to set email alerts
|

PGC‐1a integrates a metabolism and growth network linked to caloric restriction

Abstract: Deleterious changes in energy metabolism have been linked to aging and disease vulnerability, while activation of mitochondrial pathways has been linked to delayed aging by caloric restriction (CR). The basis for these associations is poorly understood, and the scope of impact of mitochondrial activation on cellular function has yet to be defined. Here, we show that mitochondrial regulator PGC‐1a is induced by CR in multiple tissues, and at the cellular level, CR‐like activation of PGC‐1a impacts a network tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…The inference is a shift toward fatty acid fuel utilization, aligning with prior reports of lipid remodeling outcomes reported in renal endothelial cells (Choi et al, 2018). These outcomes are also consistent with our genetic studies of modest PGC-1a overexpression in preadipocytes, where these same metabolic changes induced in mitochondria were linked to greater capacity for lipid fuel utilization, changes in lipid handling, lipid storage, and membrane lipid composition (Miller et al, 2019b). Anti-inflammatory actions of AdipoRon could also exert beneficial muscle outcomes as recently reported in a genetic mice model of Duchenne muscular dystrophy and warrants investigation in our aging study (Abou-Samra et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The inference is a shift toward fatty acid fuel utilization, aligning with prior reports of lipid remodeling outcomes reported in renal endothelial cells (Choi et al, 2018). These outcomes are also consistent with our genetic studies of modest PGC-1a overexpression in preadipocytes, where these same metabolic changes induced in mitochondria were linked to greater capacity for lipid fuel utilization, changes in lipid handling, lipid storage, and membrane lipid composition (Miller et al, 2019b). Anti-inflammatory actions of AdipoRon could also exert beneficial muscle outcomes as recently reported in a genetic mice model of Duchenne muscular dystrophy and warrants investigation in our aging study (Abou-Samra et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…5D). Our previous studies have shown that increased respiration is accompanied by slower growth in cultured fibroblasts (Miller et al, 2019b).…”
Section: Exercise Training Has Been Reported To Induce the Expression Of The Canonical Promoter Drivenmentioning
confidence: 94%
See 1 more Smart Citation
“…44) PKM2 activators can promote the formation of its tetramer, reduce nuclear transcription, inhibit the production of pro-inflammatory M1-type macrophages induced by LPS, and promote the production of anti-inflammatory M2type macrophages. 46,47) Our data indicated that NOR could inhibit the increase of PKM2 nuclear transcription and HIF-1α expression induced by LPS, which may be the underlying mechanism of activating M2-type macrophages. PGC-1α plays an important role in oxidative metabolism, promoting oxidative phosphorylation and mitochondrial proliferation.…”
Section: Discussionmentioning
confidence: 72%
“…Growth pathways are integral in cell fate, functional dynamics including cytoskeleton assembly and organization, energetics, and growth. Studies in cells and in tissues of genetically diverse mice confirm the integration of metabolism and growth networks and indicate that mitochondria might be drivers rather than passengers in the aging process (Miller et al, 2019). An emerging theme from our work and that of others is the complex interplay between metabolic and growth regulation where changes in each define the range of response in the other, and both are coordinated through nutrient availability and nutrient-sensitive signaling (Bartke, 2017;Finkel, 2015;Ma and Gladyshev, 2017;Souder and Anderson, 2019).…”
Section: Discussionmentioning
confidence: 96%